Introduction: From the idea of Africa to the African idea of Africa - Sabelo J. Ndlovu-Gatsheni; Bongani Ngqulunga (The Thinker)
This special issue is part of the collaborative research project initiated by the Chair in Epistemologies of the Global South with Emphasis on Africa, based at the University of Bayreuth in Germany, and the Johannesburg Institute for Advanced Study (JIAS), based at the University of Johannesburg in South Africa. The collaborative project is entitled “The Changing African Idea of Africa and the Future of African Studies.” At the University of Bayreuth, the research project is also part of The African Multiple Cluster of Excellence supported by the Deutsche Forschungsgemeinschaft (grant number EX 20521-390713894). The overarching agenda of The African Multiple Cluster of Excellence is that of reconfiguring African Studies, and at the centre of this is the imperative of doing African Studies with Africans while also privileging African voices and intellectual/academic productions.